M. tuberculosis relies on trace oxygen to maintain energy homeostasis and survive in hypoxic environments - Kalia, Nitin Pal (2023)
The bioenergetic mechanisms by which Mycobacterium tuberculosis survives hypoxia are poorly understood. Current models assume that the bacterium shifts to an alternate electron acceptor or fermentation to maintain membrane potential and ATP synthesis. Counterintuitively, we find here that oxygen itself is the principal terminal electron acceptor during hypoxic dormancy. M. tuberculosis can metabolize oxygen efficiently at least two orders of magnitude below the concentration predicted to occur in hypoxic lung granulomas. Despite a difference in apparent affinity for oxygen, both the cytochrome bcc:aa3 and cytochrome bd oxidase respiratory branches are required for hypoxic respiration. Simultaneous inhibition of both oxidases blocks oxygen consumption, reduces ATP levels, and kills M. tuberculosis under hypoxia. The capacity of mycobacteria to scavenge trace levels of oxygen, coupled with the absence of complex regulatory mechanisms to achieve hierarchal control of the terminal oxidases, may be a key determinant of long-term M. tuberculosis survival in hypoxic lung granulomas.